High Dosages of Equine Chorionic Gonadotropin Exert Adverse Effects on the Developmental Competence of IVF-Derived Mouse Embryos and Cause Oxidative Stress-Induced Aneuploidy - Lin, En; Li, Zhiling; Huang, Yue; Ru, Gaizhen; He, Pei (Frontiers in Cell and Developmental Biology, 2021)
Gonadotropins play a vital role in the regulation of female reproductive ability and fertility. Our study aimed to determine the effects of superovulation with increases in equine chorionic gonadotropin (eCG; also referred to as PMSG) dosages on the developmental competence of mouse embryos and aneuploidy formation during in vitro fertilization (IVF). Increases in the eCG dose enhanced the oocyte yield retrieved from each mouse in a dose-response relationship. The administration of 15 IU eCG significantly reduced the fertilization rate and the formation of four-cell embryos and blastocysts and increased the risk of chromosome aneuploidy. The IVF-derived blastocysts in the 15 IU eCG treatment group had the lowest number of total cells, inner cell masses (ICMs) and trophectoderm (TE) cells. Moreover, more blastocysts accompanied by fewer apoptotic cells were observed in the 0, 5 and 10 IU eCG treatment groups than in the 15 IU eCG treatment group. We also investigated the reactive oxygen species (ROS) levels and the variations in various variables: the mitochondrial membrane potential (MMP); numbers of active mitochondria; mitochondrial superoxide production; adenosine triphosphate (ATP) content; spindle structures; chromosome karyotypes; microfilament distribution; expression of Aurora B, which is an important component of the chromosomal passenger complex (CPC); spindle assembly checkpoint (SAC) protein mitotic arrest deficient like 1 (MAD2L1); and the DNA damage response (DDR) protein γH2AX. The injection of 15 IU eCG increased the level of ROS, rapidly reduced the MMP, increased the levels of active mitochondria and mitochondrial superoxide production, reduced the ATP content, increased the rate of abnormal spindle formation, and induced abnormalities in the chromosome number and the microfilament distribution, suggesting that a high dose of eCG might alter developmental competence and exert negative effects on IVF-obtained mouse embryos. Additionally, the appearance of γH2AX and the significantly increased expression of Aurora B and MAD2L1 suggested that the administration of higher dosages of eCG caused ROS-induced DNA damage-triggered Aurora B‐mediated SAC activation in early mouse IVF-derived embryos for the self-correction of aneuploidy formation. This study can improve our understanding of the application of gonadotropin and provide a theoretical basis for gonadotropin treatment.